2022
DOI: 10.3390/ijerph192013237
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Relationship between Workload and Injury Risk of Professional Male Soccer Players

Abstract: The number of studies on the relationship between training and competition load and injury has increased exponentially in recent years, and it is also widely studied by researchers in the field of professional soccer. In order to provide practical guidance for workload management and injury prevention in professional athletes, this study provides a review of the literature on the effect of load on injury risk, injury prediction, and interpretation mechanisms. The results of the research show that: (1) It appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
(121 reference statements)
0
7
0
1
Order By: Relevance
“…and the associated internal response load (e.g., heart rate, perception of effort). Long-as well as short-term increases in internal load have been shown to be associated with over-training (11), increased risk of injury (12), and increased need for rest and recovery (13). Similarly, sudden changes in normal routines (e.g., extensive travelling, fixture congestion etc.)…”
Section: Introductionmentioning
confidence: 99%
“…and the associated internal response load (e.g., heart rate, perception of effort). Long-as well as short-term increases in internal load have been shown to be associated with over-training (11), increased risk of injury (12), and increased need for rest and recovery (13). Similarly, sudden changes in normal routines (e.g., extensive travelling, fixture congestion etc.)…”
Section: Introductionmentioning
confidence: 99%
“…30 When considering workload, previous data have indicated that increased workloads are associated with injury in numerous lower extremity sports such as rugby and soccer (futbol). 15,17,46 However, limited data are available on the concept of workload and its application to baseball players and pitchers. 27,28 A further understanding of workload is also important given potential confusion of how to define workload in a baseball pitcher.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, TD, HSR, ACC, and DEC are predictive factors of players' risk of injury [36].The relationship between external load and the likelihood of sports injury occurrence has recently been discussed using those GPS metrics [25,[37][38][39][40][41]. Indeed, a recent systematic review on this topic reinforced the importance of monitoring players' external load across training sessions [27]. Regarding the analyzed external load metrics, our results sustained that the players are more prone to suffer any type of sports injuries due to a significant increase in TD, HSR, ACC, and DEC, when comparing the average of a four-week block before the injury with the seasonal average and the fourweek block after clinical discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we aimed to calculate the season average value as a representative variable of the full conditions of the season, without the exception of any conditioning factors that players and coaches cannot control. Thus, the choice of these time periods is related to the fact that most of the recent studies in this area have followed these guidelines, as can be seen in a recent systematic review of professional football players on the topic of workloads and injury risk [27]. Therefore, it becomes possible to compare results and draw conclusions and reflections from what happened with scientific studies in the same area.…”
Section: Experimental Approachmentioning
confidence: 99%